Non degenerative disease in MRI cervical spine of symptomatic patients - Karki, Dan B; Panta, Om Biju; Gurung, Ghanashyam (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: The most common etiology of neck pain is degenerative disc disease, however non-degenerative disease can be important cause of neck pain. This study aims to study the non-degenerative findings in cervical MRI in symptomatic patients with neck and radicular pain. Materials & Methods: The study was a institutional record based retrospective study performed for the duration of 3 years. MRI performed for patients with neck pain and/ or radiculopathy were reviewed. Patients with post operative findings were excluded from the study. Statistical analysis was done using SPSS 21.0. Results: A total of 721 MRI were performed for neck pain and radiculopathy, among which 91 (12.13%) cases had non-degenerative changes. Most common non degenerative change was traumatic lesions followed by neoplastic lesions and syrinx. Traumatic lesions were more common in males as compared to females. Infection was more common in females as compared to males. C5 and C6 vertebrae were most common vertebra involved in trauma and infection. Some cases like signal change in spinal cord, and syrinx were also noted in our study. Conclusion: Non degenerative cause of neck pain were less common but important cause of neck pain. Traumatic lesions were the most common cause of non degenerative neck pain. Journal of College of Medical Sciences-Nepal, Vol.11(4) 2015: 20-23